Are Attributes of Pregnancy and the Delivery Room Experience Related to Development of Autism? A Review of the Perinatal and Labor Risk Factors and Autism. (1st October 2014) - Dhawan, Naveen; Emerson, Blaze; Popara, Romana; Lin, Catherine; Rawji, Adam; Zeiden, Rita; Rashid, Leeda; Phyu, Pwint; Bahl, Jaya; Gupta, Vineet
Abstract : Autism is a neurodevelopmental disorder marked by severe deficits in social communication and interactions. It is a complex condition that lacks an established preventive method, warranting a need for research to identify possible environmental triggers. The identification of external factors particularly perinatal risk factors forms the initial critical step in preventing and alleviating risks. We conducted a literature review to assess evidence suggested in the worldwide literature. Perinatal risk factors that have a suggested association include β 2 adrenergic receptor agonists, labor induction and augmentation, maternal infection and disease (i.e., antiphospholipid syndrome), antiepileptic drugs, cocaine use, and oral supplements. Smoking has not been found to have a direct association. Pollutants, selective serotonin reuptake inhibitors, artificial insemination, and fertility medications may have a link, but results are often conflicted. Factors related to the delivery room experience may be associated with meconium aspiration syndrome, birth weight, and labor time. Several risk factors during the pregnancy and labor periods have been associated with autism; yet further studies with large populations are needed to establish definitive associations. The fact that several risk factors during the prenatal and labor periods are implicated in autism should prompt the medical community to focus on the pregnancy and labor periods as preventive measures to curb the incidence of autism.